2005
DOI: 10.17221/4166-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Sub-indexes for bulls ofHolsteinbreed in the Czech Republic

Abstract: Sub-indexes were constructed for bulls of the Holstein breed according to groups of production traits -production index for milk (IPH), sub-indexes for reproduction (IRH), longevity (IDH), health resistance (IOH) and fitness (IFH). Every index for selection for a group of traits applies all available information -breeding values for traits of milk performance, fertility and linear type trait classification. The sub-indexes were compared with the total index (SIH). The accuracy of total selection index (SIH) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Similar findings were presented by BOUšKA et al (1999). BOUšKA et al (2006) demonstrated that the objective of breeding systems is to maximize the overall herd profit, and therefore they evaluated positively the inclusion of udder traits in the total selection indexes used in the Czech Republic as reported by šAFUS et al (2005). The selection is made according to hereditary disposition, which is defined by the breeding value of selected traits (BEZDíčEK et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Similar findings were presented by BOUšKA et al (1999). BOUšKA et al (2006) demonstrated that the objective of breeding systems is to maximize the overall herd profit, and therefore they evaluated positively the inclusion of udder traits in the total selection indexes used in the Czech Republic as reported by šAFUS et al (2005). The selection is made according to hereditary disposition, which is defined by the breeding value of selected traits (BEZDíčEK et al 2008).…”
Section: Resultsmentioning
confidence: 99%